Exercise performance is regulated during repeated sprints to limit the development of peripheral fatigue beyond a critical threshold - Hureau, T. J.; Olivier, N.; Millet, G. Y.; Meste, O.; Blain, G. M. (Experimental Physiology, 2014)
We hypothesized that exercise performance is adjusted during repeated sprints in order not to surpass a critical threshold of peripheral fatigue. Twelve men randomly performed three experimental sessions on different days, i.e. one single 10 s all-out sprint and two trials of 10 × 10 s all-out sprints with 30 s of passive recovery in between. One trial was performed in the unfatigued state (CTRL) and one following electrically induced quadriceps muscle fatigue (FTNMES). Peripheral fatigue was quantified by comparing pre- with postexercise changes in potentiated quadriceps twitch force (DeltaQtw-pot) evoked by supramaximal magnetic stimulation of the femoral nerve. Central fatigue was estimated by comparing pre- with postexercise voluntary activation of quadriceps motor units. The root mean square (RMS) of the vastus lateralis and vastus medialis EMG normalized to maximal M-wave amplitude (RMS.Mmax-1) was also calculated during sprints. Compared with CTRL condition, pre-existing quadriceps muscle fatigue in FTNMES (DeltaQtw-pot = -29 ± 4%) resulted in a significant (P < 0.05) reduction in power output (-4.0 ± 0.9%) associated with a reduction in RMS.Mmax-1. However, DeltaQtw-pot postsprints decreased by 51% in both conditions, indicating that the level of peripheral fatigue was identical and independent of the degree of pre-existing fatigue. Our findings show that power output and cycling EMG are adjusted during exercise in order to limit the development of peripheral fatigue beyond a constant threshold. We hypothesize that the contribution of peripheral fatigue to exercise limitation involves a reduction in central motor drive in addition to the impairment in muscular function.